2019
DOI: 10.1039/c9gc02120e
|View full text |Cite|
|
Sign up to set email alerts
|

Sulfonated graphitic carbon nitride as a highly selective and efficient heterogeneous catalyst for the conversion of biomass-derived saccharides to 5-hydroxymethylfurfural in green solvents

Abstract: Sulfonated graphitic carbon nitride having both Brønsted base and Brønsted acid sites is used as a heterogeneous catalyst for the selective conversion of different biomass-derived saccharides to 5-hydroxymethylfurfural in green solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 66 publications
8
77
0
Order By: Relevance
“…Among them, those utilizing carbon nitride‐based photocatalysts as photocatalysts have attracted particular attention. Chhabra et al [135] . developed a sulfonated g‐C 3 N 4 (S‐GCN) for the evolution of 5‐HMF from biomass‐based saccharides.…”
Section: Application Of Carbon Nitride‐based Photocatalysts In Biomass Reformingmentioning
confidence: 99%
“…Among them, those utilizing carbon nitride‐based photocatalysts as photocatalysts have attracted particular attention. Chhabra et al [135] . developed a sulfonated g‐C 3 N 4 (S‐GCN) for the evolution of 5‐HMF from biomass‐based saccharides.…”
Section: Application Of Carbon Nitride‐based Photocatalysts In Biomass Reformingmentioning
confidence: 99%
“…g‐CN is also metal‐free carbon nanomaterial with some superior properties, such as high thermal (up to 600 °C in oxygen, nitrogen, or air atmosphere) and chemical stability. [ 70 ] Under calcination conditions, g‐CN can be easily made from low‐priced nitrogen‐rich precursors (urea, cyanamide, cyanuric acid, thiourea, dicyandiamide, and melamine). [ 71 ] Among the precursors, urea is most commonly used as a precursor due to its appealing properties, such as low cost, nontoxicity, and abundant availability.…”
Section: Sulfonated Carbon‐based Catalysts For Biodiesel Productionmentioning
confidence: 99%
“…Following the lead from earlier studies emanating from Varma's group, Krishnan and co-workers [55] recently reported the preparation of a sulfonated g-C 3 N 4 with an amphoteric character possessing both Brønsted acid and basic sites. Firstly, they performed the optimization reactions using the dehydration of glucose to produce HMF, achieving a maximum yield of 94 %.…”
Section: Acid-catalyzed Reactionsmentioning
confidence: 99%